American biblical archaeology and Zionism: the politics of objectivity from William F. Albright to William G. Dever - Sherrard, Brooke (Copenhagen international seminar, 2023)
"This book examines the relationship between several of the most prominent American biblical archaeologists and Zionism. While these scholars have been studied and historicized to some extent, little work has been done to understand their role in the history of the Palestinian-Israeli conflict. Two defining differences in the archaeologists' arguments were their understanding of culture and their views on objectivity versus relativism. Brooke Sherrard Knorr argues that relativist archaeologists envisioned the ancient world as replete with cultural change and opposed the establishment of a Jewish state, while those who believed in scholarly objectivity both envisioned the ancient world's ethnic boundaries as rigid and favored Zionism. Combining readings of the archaeologists' writings with archival research, this book studies the views of William Foxwell Albright, Millar Burrows, Nelson Glueck, George Ernest Wright, Paul Lapp, and William G. Dever regarding the establishment of an ethno-national state in Palestine in detail. The volume culminates with an epilogue commenting on the relevance of this topic in the present regarding the political ramifications of archaeology in the Israeli-Palestinian conflict. American Biblical Archaeology and Zionism is of interest to students and scholars of Biblical and Near Eastern archaeology, American religious history, and the Israeli-Palestinian conflict, particularly its role in regional archaeology"--